2021
DOI: 10.3390/en14030522
|View full text |Cite
|
Sign up to set email alerts
|

Reduction of Power Imbalances Using Battery Energy Storage System in a Bulk Power System with Extremely Large Photovoltaics Interactions

Abstract: Power imbalances such as power shortfalls and photovoltaic (PV) curtailments have become a major problem in conventional power systems due to the introduction of renewable energy sources. There can be large power shortfalls and PV curtailments because of PV forecasting errors. These imbalances might increase when installed PV capacity increases. This study proposes a new scheduling method to reduce power shortfalls and PV curtailments in a PV integrated large power system with a battery energy storage system (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
23
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(23 citation statements)
references
References 28 publications
0
23
0
Order By: Relevance
“…The power system model of the Kanto area of Japan is used in this study [28]. The maximum demand in this test system is approximately 60 GW.…”
Section: Simulation Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The power system model of the Kanto area of Japan is used in this study [28]. The maximum demand in this test system is approximately 60 GW.…”
Section: Simulation Resultsmentioning
confidence: 99%
“…The system consists of 168 dispatchable thermal generators and un-dispatchable nuclear, hydropower sources, and Solar PV. The parameters used in the tests are given below [28], [31].…”
Section: Simulation Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The difference in importance of energy storage can be explained as it was not owned and operated by the market party, but rather operated by the TSO, which lead to significant variation in re-dispatch costs. Another study demonstrated that proper management of battery energy storage can reduce curtailment losses, also for high penetration of PV electricity [30].…”
Section: Introductionmentioning
confidence: 99%
“…It is clear that by decreasing the maximum power output of a PV system actively or passively, the pressure on the transmission or distribution grid will decrease [31]. Batteries can be used to temporarily store the electricity at peak generation moments [23,30,32]. In this study Li-ion batteries are considered as they can be considered a mature technology [33][34][35].…”
Section: Introductionmentioning
confidence: 99%